ANALISIS KESEHATAN BANK DENGAN METODE CAMELS ( Kasus Pada PT. Bank Riaukepri Persero Tbk. Cabang Utama Pekanbaru Tahun 2013) - ", Hermawanti; Zuliarni, Sri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
Banking has a very important role for the economy of the community, its existence is able to simplify and accelerate the need for financial transactions and economic activity throughout the community, so it becomes very strategic banking business and compete in maintaining its existence. Bank health becomes very important for the economy needs to grow and thrive. Therefore, Bank Indonesia as the regulator and supervisor directs the activities of the bank's operational policy development with the provision of banking system in assessing the level of health should be measured by the bank's management in order to achieve the stability of the financial system in order to promote national economic growth.This research is a quantitative descriptive study in order to determine and analyze the health of banks commercial banks in PT. Bank Riaukepri Persero Tbk. Main Branch Pekanbaru in 2013 by using the CAMELS method.The method of measuring the level of health by using ratios as indicators of CAR, KAP, NPM, ROA, LDR, and IER on the bank's financial statements as the primary data. Results of research conducted on the average yield ratio and rank placement of components and factors of each factor indicates the PT. Bank Riaukepri Persero Tbk. Main Branch in 2013 Pekanbaru is rated "Healthy" or being in the Composite Rating (PK-2).Keywords: Bank of Health, CAMELS analysis methods, Ratio